2012
DOI: 10.2174/092986712803414105
|View full text |Cite
|
Sign up to set email alerts
|

Small Intestinal Injury Caused by NSAIDs/Aspirin: Finding New from Old

Abstract: Small intestinal injury caused by non-steroidal anti-inflammatory drugs (NSAIDs) or aspirin is an epoch making topic in clinical field with the aid of new devices, capsule endoscopy and double balloon enteroscopy to look at small intestine directly. However, the injury has been reported in animals since more than 40 years ago. Proposed mechanisms are impairment of mucosal defense through inhibition of cyclooxygenase (COX) resulting in deficiency of prostaglandins, and mitochondrial disorder. Possible aggressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 41 publications
1
23
1
2
Order By: Relevance
“…Oral administration of aspirin does not cause small intestinal epithelial cellular injury directly because aspirin is rapidly absorbed from the stomach and duodenum under acidic conditions and because of the lack of enterohepatic recirculation [7]. However, recent enteroscopic studies have clearly demonstrated that low-dose aspirin (usually enteric-coated) induces hemorrhagic lesions, including ulcers and bleeding, in the small intestine in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Oral administration of aspirin does not cause small intestinal epithelial cellular injury directly because aspirin is rapidly absorbed from the stomach and duodenum under acidic conditions and because of the lack of enterohepatic recirculation [7]. However, recent enteroscopic studies have clearly demonstrated that low-dose aspirin (usually enteric-coated) induces hemorrhagic lesions, including ulcers and bleeding, in the small intestine in patients.…”
Section: Discussionmentioning
confidence: 99%
“…TNF has been reported to up-regulate the expression of nucleotide-binding oligomerization domain 2 (NOD2) gene in intestinal epithelial cells leading to subsequent increase in their lipopolysaccharide (LPS) susceptibility [75]. LPS, which is a highly pathogenic component of the walls of gram-negative bacteria has been reported to mediate the release of TNF from macrophages via MyD88 through Toll like receptor (TLR)-4 [134,137]. Similar rise in the level of TNF was observed in the small intestine of mice given indomethacin [134,138,139].…”
Section: Relationship Between Nsaids Tnf and Bacteriamentioning
confidence: 99%
“…While, targeting enteric bacteria with a poorly absorbed antibiotic (like rifaximin), covering gram-positive and gram-negative bacteria (both aerobic and anaerobic) has been reported to attenuate the myeloperoxidase (MPO) and TNF tissue levels [140]. However, if left untreated, this consistent rise in TNF also activates neutrophils, which once entered the bowel microcirculation, undergo a rapid activation leading to tissue invasion, with massive production of injurious substances such as proteolytic enzymes and detrimental ROS leading to exacerbation of small intestinal injury [137]. [134,137].…”
Section: Relationship Between Nsaids Tnf and Bacteriamentioning
confidence: 99%
“…По-вреждение клеточных мембран и расширение межклеточных пространств эпителия увеличивают проницаемость последнего для желчных кислот и протеолитических ферментов. Следствием нарушения барьерной функции СО кишки также становится транслокация энтеробактерий с дальнейшей интенсификацией воспалительного процесса [18].…”
Section: терапевтический архив 12 2014unclassified